Uncovering Patterns of Green Behavior: A Cluster and Factor Analysis of Sustainable Practices Among Food Micro-Businesses - Quinco, Daryl F. (Research Synergy Foundation, 2026)
This study investigates the green behavior patterns of food micro-businesses in Ozamiz City, Philippines, employing exploratory factor analysis and K-means clustering to uncover behavioral typologies based on sustainable practices. Using survey data from 4,130 micro-businesses, two main behavioral dimensions emerged: Visible Operational Practices and Internal Efficiency. A subsequent cluster analysis identified three distinct groups: Sustainability-Oriented Enterprises, Moderate Green Practitioners, and an Isolated Minimalist. Results show that while many businesses demonstrate commendable environmental efforts, others exhibit partial or superficial engagement, highlighting the limitations of uniform sustainability policies. The resulting typology functions as a practical decision framework for policymakers and development practitioners by enabling differentiated interventions—such as advanced incentives and market-based support for sustainability-oriented enterprises, capacity-building and technical assistance for moderate practitioners, and foundational awareness, mentoring, and regulatory guidance for minimal adopters. By explicitly linking behavioral readiness to tailored policy and programmatic responses, this study moves beyond one-size-fits-all sustainability approaches and supports more efficient, context-sensitive, and scalable green enterprise development in developing economies.